MPS Manager: A Serious Game to Enhance Teaching on Software Development Process Quality - Iago Rodrigues Agualuza; Silvana Morita Melo; Lina Garcés; Vânia de Oliveira Neves (Informatics in Education)
Modern software companies prioritize high-quality products for competitiveness, and Software Process Improvement (SPI) models help achieve this. In Brazil, the Brazilian Software Process Improvement Model (MPS-SW model) is widely used, but its complexity and extensive documentation make it challenging to teach in undergraduate courses. To address the lack of students engagement to learn SPI, we developed the MPS Manager, a serious game that incorporates gamification to facilitate learning about the MPS-SW model. The game was evaluated in four Software Engineering courses across three universities with 83 students. Using the Model for the Evaluation of Educational GAmes (MEEGA+) method, students assessed the game across dimensions such as usability, confidence, and learning, with 55% overall agreement. Further analysis explored correlations between satisfaction and factors like gender, gaming experience, and course format (i.e., virtual or in-person). Feedback from students highlighted the need for improved engagement, social interaction, and reduced gameplay monotony, which will guide future game enhancements.